Büyük Nutuk’ un genel olarak incelenmesi - Karaçizmeli, Lütfiye (My University, 1990)
unknown
Keywords: Atatürk, Gazi Mustafa Kemal, Türkiye Cum. Bşk., 1, 1881-1938; Atatürk, Mustafa Kemal, President of the Republic of Turkey 1, 1881-1938